Privacy in Cyberspace: Islamic Republic of Iran Perspective - YAVARI, Asadollah; MAZINANIAN, Saeedeh (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
Privacy is one of the cornerstones of the realization of human rights in a democratic system and is defined as a realm of everyone's life, is not accessible to others. Thus, privacy in cyberspace has a similar definition. Since privacy and data protection have different definitions for business owners, governments, and the general public, unlike other areas of law, which have well-established legal concepts, norms, and principles, privacy and data protection is an area of law that is not currently consolidated. The right to privacy, therefore, falls into two normative frameworks: preventing violation of the privacy of others, and training and guidance on secrecy. Data protection and privacy are not limited to one legal area. Data protection and privacy laws include areas of intellectual property, competition, and part of cybercrime. Since the level of individuals' privacy is determined by the national laws of each country or political entities such as the European Court of Human Rights (ECtHR) and the European Court of Justice, through the EU's General Data Protection Regulations applicable since 2018, the European Union (EU) has set criteria that will have a major impact on data protection and privacy laws in other countries. Furthermore, as privacy is one of the strongest recommendations of Islam, the law of cybercrime (2009), the law of freedom to access to information (2010), the charter of citizens' rights (2016) is supported in the positive laws of the Islamic Republic of Iran as well as in the constitution. The most important question in this article is what is the scope of privacy in cyberspace and to what extent do laws and regulations support it? Therefore, this descriptive-analytical study analyzes the concept of privacy and the scope of its right in the laws and regulations of the Islamic Republic of Iran and the challenges that the right of privacy faces.